Medical Management of Emphysematous Gastritis - Farshad Ghasemi; Iain Kirkpatrick; Aditya Sharma (Annals of Internal Medicine: Clinical Cases)
A 95-year-old man presented to the hospital with altered mental status, sepsis, and coffee-ground emesis. His chest radiograph showed gas along the lesser curvature of the stomach, prompting abdominal computed tomography, which demonstrated intramural gastric air. This patient's clinical presentation and computed tomography findings were suggestive of emphysematous gastritis (EG). He was successfully managed with an intravenous proton-pump inhibitor and broad-spectrum antibiotics. Details of the case are presented to encourage the early diagnosis of EG, which may make conservative management more successful.